Myanmar Agricultural Performance Survey Round Two: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Myanmar Agricultural Performance Survey (MAPS) Round 2 is a sub-sample survey carried out during the Dry (pre/post monsoon) Season of 2022 that includes farming households from the Myanmar Household Welfare Survey (MHWS). MHWS is a nationally and sub‐nationally representative phone survey with the objective of collecting quarterly data on household and individual welfare indicators, including poverty, food security, dietary quality, subjective wellbeing, and coping strategies. MAPS Round 1 sampled from the 5,465 farm households in MHWS Round 1 and completed interviews with 3,891 respondents. Round 2 used the Round 1 respondents as the initial sample and then added new farm households from MHWS R3 until a target of 5,000 respondents was exceeded. Phone surveys have several shortcomings including representativeness, enumerator trust, measurement error, and shortened survey length. To help ensure representativeness of our sample we set targets for MHWS data collection from rural, female, lower-educated, and farming households. While there are weaknesses of phone surveys, there are also advantages, particularly in Myanmar. Previous face-to-face socioeconomic surveys in Myanmar failed to reach many townships across the country either due to conflict or remoteness. Round 2 of MAPS includes 275 out of 324 townships.